Plasmon-Enhanced Fluorescence of EGFP on Short-Range Ordered Ag Nanohole Arrays - Bochenkov, Vladimir E. (Nanomaterials (Basel), 2020)
Fluorescence of organic molecules can be enhanced by plasmonic nanostructures through coupling to their locally amplified electromagnetic field, resulting in higher brightness and better photostability of fluorophores, which is particularly important for bioimaging applications involving fluorescent proteins as genetically encoded biomarkers. Here, we show that a hybrid bionanosystem comprised of a monolayer of Enhanced Green Fluorescent Protein (EGFP) covalently linked to optically thin Ag films with short-range ordered nanohole arrays can exhibit up to 6-fold increased brightness. The largest enhancement factor is observed for nanohole arrays with a propagating surface plasmon mode, tuned to overlap with both excitation and emission of EGFP. The fluorescence lifetime measurements in combination with FDTD simulations provide in-depth insight into the origin of the fluorescence enhancement, showing that the effect is due to the local amplification of the optical field near the edges of the nanoholes. Our results pave the way to improving the photophysical properties of hybrid bionanosystems based on fluorescent proteins at the interface with easily fabricated and tunable plasmonic nanostructures.